Microfabrication with smooth thin carbon nanotube composite sheets. (22nd March 2017) - Boyer, Nathan; Pei, Lei; Rowley, Joseph; Syme, Derric; Liddiard, Steven; Abbott, Jonathan; Larson, Kyle; Liang, Zhiyong; Iverson, Brian; Vanfleet, Richard; Davis, Robert
Abstract: Carbon nanotube (CNT)/polymer composite materials can be high strength, stiff, and lightweight, which makes them attractive for fabrication of micromechanical structures. Here we demonstrate a method whereby smooth, thin, high CNT concentration composite sheets can be fabricated and patterned on the microscale using a process of photolithography and plasma etching. Two types of CNT/polymer composite sheets were fabricated: one made from CNTs grown on patterned supported catalyst and one made from CNTs grown with floating catalyst; these had thicknesses of 6 µ m and 26 µ m respectively and a roughness of less than 60 nm.